Peningkatan Pemahaman terhadap Islam dan Budaya Minangkabau bagi Mahasiswa IAI SUMBAR di Batusangkar - Wandi, Joni Indra; Syamsurizal, Syamsurizal; Saputra, Edriagus; Andrianto, Andrianto; Rahmiyati, Rahmiyati (Institut Agama Islam Sumatera Barat, 2023)
This Community Service Writing (PKM) discusses the development of a field lecture program to Batusangkar, a historic area with rich Minangkabau culture and strong Islamic values. This program is part of an effort to increase students' understanding of Islam and Minangkabau Culture at the West Sumatra Islamic Institute (IAI). The method used in this service is participatory action research. The service team consists of West Sumatra IAI lecturers and students who are involved in program planning, implementation and evaluation. For two days, 92 students from 6 study programs were invited to take part in field lecture activities that were integrated with material on Islam and Minangkabau Culture. The results of this program 1. show an increase in student understanding of Islamic values ??and Minangkabau culture. 2. During field studies, students are able to directly interact with the local community, visit historical places, and explore various aspects of Minangkabau culture and traditions. 3. Through discussion and reflection, students succeed in instilling Islamic values ??in the local cultural context. In addition, this field lecture program also has a positive impact on the Pagaruyung community. With the student visits, the local community is more open to share their knowledge and experiences about Islam and their culture. The active involvement of the community also helps in mutual learning between students and the community. Although this program provides significant benefits, there are some challenges encountered during its implementation. Among them are budget constraints, logistics, and coordination with related parties. Therefore, it is suggested that this program continues to be developed and supported by all relevant parties to achieve more optimal results.